Myomas and Adenomyosis: Impact on Reproductive Outcome. (6th November 2017) - Vlahos, Nikos F.; Theodoridis, Theodoros D.; Partsinevelos, George A.
Abstract : Among uterine structural abnormalities, myomas and adenomyosis represent two distinct, though frequently coexistent entities, with a remarkable prevalence in women of reproductive age. Various mechanisms have been proposed to explain the impact of each of them on reproductive outcome. In respect to myomas, current evidence implies that submucosal ones have an adverse effect on conception and early pregnancy. A similar effect yet is not quite clear and has been suggested for intramural myomas. Still, it seems reasonable that intramural myomas greater than 4 cm in diameter may negatively impair reproductive outcome. On the contrary, subserosal myomas do not seem to have a significant impact, if any, on reproduction. The presence of submucosal and/or large intramural myomas has also been linked to adverse pregnancy outcomes. In particular increased risk for miscarriage, fetal malpresentation, placenta previa, preterm birth, placenta abruption, postpartum hemorrhage, and cesarean section has been reported. With regard to adenomyosis, besides the tentative coexistence of adenomyosis and infertility, to date a causal relationship among these conditions has not been fully confirmed. Preterm birth and preterm premature rupture of membranes, uterine rupture, postpartum hemorrhage due to uterine atony, and ectopic pregnancy have all been reported in association with adenomyosis. Further research on the impact of adenomyosis on reproductive outcome is welcome.